Urdu Poetry of Hazrat Khawaja Ghulam Fareed - Khan, Badar Nasood; Khan, Shaista Hameed (sourcecoder, 2023)
Khawaja Ghulam Fareed (1845-1901) was born at Chachran, in South Punjab. He had a spiritual ancestry with Baba Fareed Ganj-e-Shakkar. He was the mystic poet of the land. Through his Siraiki and Punjabi poetry, he wants to awake the nation towards the realistic life intellect, belonging to the universal order has a direct perception of the transcendent. It is the reality that the heart knowledge is the knowledge of the transcendent. Khawaja Fareed’s period was the tough for the Muslims in sub-continent. Through in poetry he tried to remove the depressive signs in the lives of Muslims principle. Urdu poetry of Khawaja Fareed is consistent of Ghazals. About one hundred of his Ghazals are available. Due to his ghazals, he stands in the ranks of contemporary Urdu poets. Like Siraiki Punjabi poetry, his Urdu Ghazals is also full of mysticism, love and cultural symbols and allegory. He was well aware about the dignity of man. Character of a man is worth narrating. As a lover he possess different experiences. His Urdu poetry depicts the true taste of love and harmony.